2020
DOI: 10.3892/ijmm.2020.4787
|View full text |Cite
|
Sign up to set email alerts
|

Toll‑like receptor 4 activates the NLRP3 inflammasome pathway and periodontal inflammaging by inhibiting Bmi‑1 expression

Abstract: Overproduction of pro-inflammatory cytokines in the aged, which is called inflammaging, leads to the deterioration of periodontitis. Toll-like receptor 4 (TLR4) plays a role in the regulation of cellular senescence, and its expression increases with age. However, there has been limited research into the molecular mechanisms underlying the onset of periodontal inflammaging, and the interplay between TLR4 and inflammaging. In the present study, wild-type and TLR4 gene knockout mice were used to investigate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Previous studies have noted that the periodontal cells of diabetic mice experience a chronic, low‐degree inflammatory state termed inflamm‐aging, characterized by cell senescence and SASP secretion (Qin et al, 2020; Wang et al, 2020). We have observed that p16 and p21 expressions are significantly increased in periodontal cells of diabetic mice, in agreement with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted that the periodontal cells of diabetic mice experience a chronic, low‐degree inflammatory state termed inflamm‐aging, characterized by cell senescence and SASP secretion (Qin et al, 2020; Wang et al, 2020). We have observed that p16 and p21 expressions are significantly increased in periodontal cells of diabetic mice, in agreement with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis (PD) in adults is a chronic inflammatory disease of ageing or inflammaging ( Ebersole et al., 2018 ; Qin et al., 2020 ). This is particularly striking when the National Health and Nutrition Examination Survey (NHANES) data from 2009-2010 are stratified by patient age, with PD prevalence increasing from 24.4% in adults aged 30-34 yrs., to 70.1% in those aged 65 yrs.…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis is closely associated with the development of atherosclerosis, referring to pyroptosis in endothelial cells and macrophages [14]. The NLRP3 inflammasome is one of the major sources of inflammation in age-related diseases [15]. Several types of inflammasome were notably activated in the ageing kidneys of rats [16].…”
Section: Introductionmentioning
confidence: 99%